DESAIN MULTIMEDIA GAME TEMBAK HURUF UNTUK MENINGKATKAN PEMAHAMAN BAHASA SISWA KELAS 1 SD DALAM PENGENALAN HURUF ABJAD - Ade Sri Madona; Gusnetti Gusnetti; Syofiani Syofiani (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2021)
This type of research uses research and development (R&D). Design and research development procedures using a 2-D model, namely define, design. In the validation process, the multimedia multimedia shooting game was validated by 2 experts. Based on the results of research that has been carried out, multimedia shooting game letters for the introduction of children's alphabet letters, which has obtained an assessment percentage of 82.99%, with a very valid category. The results obtained that the multimedia shooting game for letter recognition of the children's alphabet has been valid according to experts, used as a learning medium for Grade 1 Elementary School students.